Collective Endowments; Perspective of Islamic Law and Positive Law in the Construction of Mosques - Della Haerunisa; Muhammad Misbakul Munir; Muhibban; Ryan Bianda (Al-Akhbar: Jurnal Ilmiah Keislaman, 2023)
This study aims to determine collective waqf in land acquisition in mosque construction in terms of Islamic law and Positive Law. Collective waqf is carried out for the construction of the Al-Hijrah mosque in Dayyuh Village, this object is the realm of empirical research with a type of sociological juridical research using field research instruments with descriptive analysis. This research found that land acquisition for the construction of the AL-Hijrah mosque was carried out jointly or collective waqf, there was a committee that mobilized Wakif money to buy land in the construction of the mosque. The results of this study show that according to Islamic Law that the implementation of collective waqf carried out by wakif who entrust money to the committee and buy a piece of land as required by the committee has been considered wakif to control the land and the land is in waqfkan and this is legal, As for according to Law 41/2024 the practice can be seen in article 7 regarding wakif and article 16 hurup (a) and article 15 which states the necessity of full control of the wakif, if it has been controlled, the ownership can be entrusted to the nadzir who in this case the committee for the construction of the AL-Hijrah mosque. Therefore, the land waqf system at Masjid Al Hijrah is in accordance with Articles 7, 9, 16, and 22 of Law Number 41 of 2004 concerning waqf